Chronic Antithrombinaemia (Antithrombin V) with Haemorrhagic Diathesis in a Case of Rheumatoid Arthritis with Hypergammaglobulinaemia - Loeliger, A; Hers, J. F. Ph (Thrombosis and Haemostasis, 1957)
A report is represented on a 44-year-old patient suffering, since 1938, from very slowly progressive rheumatoid arthritis. Haemorrhagic manifestations have been seen since 1951 (large cutaneous and muscular haemorrhages, microhaematuria and macrohaematuria, possibly also articular haemorrhages). In addition to an extremely marked increase in γ-globulins to values above 8 g/100 ml (γ-globulins with a normal sedimentation constant S 7) a circulating anticoagulant was demonstrable, which is held responsible for the marked increase in clotting time, “prothrombin” time and thrombin time. The hypothesis is forwarded that this is a physiological anticoagulant showing a marked increase. Since it is different from the four antithrombins described by Seegers it is referred to as antithrombin-V. Antithrombin-V occurs both in the plasma and in the serum and appears to be bound to the (ß)γ-fraction. It is a thrombin inhibitor which, unlike antithrombin-II, has no direct effect on thromboplastin and thrombin formation. Antithrombin-V cannot be neutralized by protamine sulphate; it is heat-stable, not dialysable and not adsorbed onto BaSO4. Thrombelastography made it possible clearly to demonstrate that an increase in antithrombin-V is associated with a marked increase in clotting time but causes no pathological course of clot formation.Therapeutic results obtained with ACTH and cortisone are favourable: the activity of antithrombin-V decreases parallel with a decrease in γ-globulin values, and the clotting time is normalized. The patient has received, during the past 16 months, oral cortisone treatment (25 mg thrice daily), and is at present free of complaints, although clinical and laboratory findings show a gradual increase in symptoms respectively γ-globulin values with a slight increase in clotting time.The possible significance of the antithrombin-V activity in the protection against thrombo-embolism is briefly mentioned.